Economic turmoil in Asia prospects for FDI flows - Alburo, Florian A. (The Philippine Review of Business and Economics, 1998)
The economic and financial crisis that has plagued Asia since mid-1997 has left in its wake dramatic declines in output, large falls and volatile exchange rate changes, worsening poverty, and widespread social unrest owing to rising unemployment, among others. Yet it is important to remember that there are other effects that this crisis had left behind. These are the real economic dimensions of the countries that have made them achieve sustained growth rates in the past decades. These real factors are the outcomes ofand were inﬂuenced by structural changes in the region itself, which in turn have created the environment deﬁning the pace and pattern of foreign direct investment into the affected countreis. These range from the domestic policy actions taken by governments to the transformation of the Japanese economy as a driving force for FDI. Much of this structural change in the environment for FDI in the region appears to be irreversible. It is in this context that the prospects for FDI in the region and into the affected economies seem to be positive.